An active mechanical Willis meta-layer with asymmetric polarizabilities - Yangyang Chen (Nature Portfolio, 2020)
Here, the authors experimentally demonstrate abilities of a mechanical Willis meta-layer, in beams and plates, for independently engineering transmission and reflection coefficients of flexural waves in both amplitude and phase and nonreciprocal wave propagation.